A53: Natural History of Pediatric Class V Membranous Lupus Nephritis—A Serial Biopsy Study. Issue 11 (March 2014) - Canter, Debra; Eldin, Karen; Hicks, M. John; Muscal, Eyal; DeGuzman, Marietta; Wenderfer, Scott E.
Abstract : Background/Purpose: In 1998, Sorof et al. reported 28% of 60 pediatric SLE patients had class V lesions on their first biopsy and 37% had class V lesions on their most recent biopsy. Although 19% of patients with LN transformed from other classes to class V, there were no patients with repeat biopsies who showed complete resolution of their class V lesions. The prognosis of the patients with class V LN was better than those with non‐class V LN (only 5% vs. 21% developed renal dysfunction or died). Methods: We retrospectively reviewed pathology records of pediatric lupus nephritis patients who underwent renal biopsies at Texas Children's Hospital between 1990 and 2013. Results: A total of 321 biopsies were performed on 174 patients with SLE. The cumulative incidence of class V histopathology was 50% (160/321). Upon initial biopsy, 93/174 (53%) patients had Class II, III or IV LN without class V lesions, and 81/174 (47%) patients had class V lesions, either alone (n = 38), or associated with class II, III or IV LN (n = 43). Repeat biopsies were obtained in 97 cases. The median interval between first and second biopsies was 11 months (IQR 9–19m, range 3–110 m). Of the 97 patients with at least 2 renal biopsies, 36 (37%) had class V lesions on the initial biopsy, and 61 (63%) did not have class V lesions on the initial biopsy. Although transformation between classes was common, the initially non‐class V LN patients frequently remained free of class V lesions at follow up (n = 42, 70%). Of the 18/61 initially non‐class V LN patients who did later develop class V lesions, 6% initially had pure class II LN, 61% pure class III, and 33% pure class IV. Repeat biopsies revealed mixed class V LN in 16/18 patients, with subsequent resolution of class V lesions or transformation to pure class V in 4. Six (17%) of the 36 patients with class V lesions on the initial biopsy had pure class V lesions, and 30 (83%) had mixed class II, III or IV LNThree (50%) of the 6 patients with initially pure class V lesions showed evolution to mixed class III/V LN, and evolution to class IV with sustained absence of class V lesions in 1 (17%). Of the 30 patients with initially mixed class V LN, repeat biopsies revealed persistent mixed class V LN in 22 (73%), transformation to pure class V in 4 (13%) and sustained resolution of class V lesions in 4 (13%). Conclusion: A comparison of the WHO classification of initial and repeat biopsies showed evolution to pure class V LN, or more commonly, development of a mixed class including class V LN. Although the vast majority of patients with class V LN showed persistence of this histopathology, sustained resolution of class V lesions may be possible.